“KELUARGA SEHAT PEDULI STUNTING” (OPTIMALISASI KESEHATAN KELUARGA BERBASIS KESADARAN DAN PENGELOLAAN SUMBER PANGAN SEHAT DALAM MENJAGA STATUS GIZI PADA ANAK) - S.Kep., Ns., M.Kep., Ainul; Al Faqih, S.Kep., Ns., M.Kep., Mohamad; Hadi Sulistyo, S.Kep., Ns., M.NS., Angger; S.Kep., Ns., M.Kep., Ikha (LPPM ISTeK ICsada Bojonegoro, 2024)
10 This program is the second program after the family assistance program with stunting toddlers in Sidobandung village which is considered effective in increasing children's weight and TB and increasing parents' knowledge about stunting. Stunting is a health problem that has complex causes. Not only from a parent's cognitive perspective regarding the importance of fulfilling nutrition, but also parents' behavior and compliance in fulfilling children's nutrition. However, the problem of stunting can also be triggered by economic problems. This causes families to be unable to provide appropriate nutrition for children. Therefore, we collaborate with several parties to provide support for this program. The method used is to provide outreach to lecturers and students as implementers as well as mapping the location that will be the target of the program, namely in Bulu village, Balen subdistrict, Bojonegoro. The program carried out shows concern for the community to know the ability to carry out self-care, especially at the fam ily level in preventing stunting. An assessment of the health profile and independence status is carried out to contribute to the family providing information about the client/family's self-care abilities. So that families understand about stunting and how to avoid it.